1.
a)
[tex]2x^3+x^2-6x-3 =\\x^2(2x+1)-3(2x+1)=\\(x^2-3)(2x+1)=\\(x-\sqrt3)(x+\sqrt3)(2x+1)[/tex]
b)
[tex]-x^3+4x^2+4x-16=\\-x^2(x-4)+4(x-4)=\\(-x^2+4)(x-4)=\\-(x^2-4)(x-4)=\\-(x-2)(x+2)(x-4)[/tex]
2.
[tex]f(x)=\frac{x}{x-2}\\\text{Asymptota pionowa: } x=2\\\text{Asymptota pozioma: } y=1[/tex]
[tex]f(x)=\frac{x}{x+2}\\\text{Asymptota pionowa: } x=-2\\\text{Asymptota pozioma: } y=1[/tex]
3.
Wszystkie rzuty dwiema kostkami: [tex]\Omega=6^2=36[/tex]
Zdarzenia niesprzyjajace: 12 oczek: [tex]B=(6; 6)[/tex]
Zdarzenia sprzyjające: [tex]A=36-1=35[/tex]
[tex]P(A)=\frac{35}{36}[/tex]